Ostertagia spp., rumen fluke and liver fluke single- and poly-infections in cattle: an abattoir study of prevalence and production impacts in England and Wales - Bellet, Camille; Green, Martin J.; Vickers, M.; Forbes, A.; Berry, J.; Kaler, Jasmeet (Elsevier, 2016)
This study aims at investigating the occurrence, risk factors and production impacts on beef carcassparameters of three of the most important cattle helminth infections in England and Wales. Abomasa, reticulorumens and livers from healthy cattle were collected and examined post-mortem quarterly over a one year period in an abattoir in South-West England. Specific viscera from 974 cattle were collected,examined and scored for Ostertagia spp., adult rumen fluke and liver fluke lesions/presence. A total of89%, 25% and 29% of the carcasses had lesions/presence of Ostertagia spp., rumen fluke and liver fluke, respectively, and 39% had presence of helminth co-infection. Animal demographic and carcass parameters associated with helminth infections were investigated using multi level multinomial and multilevel linear mixed models respectively. After adjusting for other factors, significant differences in the distribution of helminth infections were observed among cattle by type of breed, animal category (cow, heifer, steer and young bull), age, season and concurrent helminth infections. Compared to carcasses free of helminths, carcasses presenting solely Ostertagia Spp. lesions or adult rumen fluke had significantly lower cold carcass weight (coef.: −30.58 [−50.92;−10.24] and −50.34 [−88.50;−12.18]) and fat cover-age (coef.: −3.28 [−5.56;−1.00] and −5.49 [−10.28;−0.69]) and carcasses presenting solely liver flukelesions had significantly lower conformation grade (coef.: −3.65 [−6.98;−0.32]). Presence of helminth poly-infections was negatively associated with cold carcass weight.